LIQUID WASTE PROCESSING FOOD PROCESSING INDUSTRY, CASE STUDY PT. XYZ - Halim, Abdul; Yudiastuti, Silvia Oktavia Nur; Pangestu, Danar Pujo (Sustainable Environmental and Optimizing Industry Journal, 2023)
Processing of liquid waste needs to be done before the waste is suitable for disposal into the environment, so it does not pollute the environment. The purpose of wastewater treatment is to reduce BOD and COD levels, mixed particles, and kill pathogenic organisms. In addition, wastewater treatment also aims to remove nutrients, toxic components and materials that cannot be decomposed. In handling liquid waste, there are many ways and methods that can be used to treat the liquid waste properly. PT. XYZ uses a Wastewater Treatment Plant (WWTP), which is an installation specially designed to treat industrial waste water. Physical, chemical and biological processes are applied to the WWTP. This paper aims to review these processes in the WWTP used. PT. XYZ is a manufacturing company engaged in the food sector, which produces ice cream products with various variants and flavors. But besides producing products with good quality, PT. XYZ is also able to process its waste properly. PT. XYZ there are two kinds of solid waste and liquid waste